2018
DOI: 10.1038/s41598-017-18436-1
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of hormonal therapy with silastic tubing for prevention and treatment of breast cancer

Abstract: Broad use of germline testing has identified an increasing number of women at risk for breast cancer with a need for effective chemoprevention. We report a novel method to selectively deliver various anti-estrogens at high drug levels to the breast tissue by implanting a device comprised of silastic tubing. Optimized tubing properties allow elution of otherwise poorly bioavailable anti-estrogens, such as fulvestrant, into mammary tissue in vitro and in vivo with levels sufficient to inhibit estrogen receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
(39 reference statements)
2
8
0
Order By: Relevance
“…Together, these findings suggest that an implant reformulated to deliver greater rates of fulvestrant for a longer duration could provide comparable risk reduction to systemic therapy. This and previous studies with silicone-based tubing implants demonstrate fulvestrant is released with zero order kinetics (DNS and Park et al 21 ). Increasing the amount of fulvestrant in an implant extends the duration of release, while decreasing tubing wall thickness increases the release rate.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Together, these findings suggest that an implant reformulated to deliver greater rates of fulvestrant for a longer duration could provide comparable risk reduction to systemic therapy. This and previous studies with silicone-based tubing implants demonstrate fulvestrant is released with zero order kinetics (DNS and Park et al 21 ). Increasing the amount of fulvestrant in an implant extends the duration of release, while decreasing tubing wall thickness increases the release rate.…”
Section: Discussionsupporting
confidence: 82%
“…Fulvestrant was chosen as the active agent to be delivered due to its proven efficacy in patients, relative potency against the estrogen receptor, high lipophilicity, not requiring metabolism, unlike tamoxifen, to be fully active, as well as its long-established safety history 20 . This proof of principle study demonstrated that when sealed within the lumen of silicone tubing, fulvestrant exhibited zero order elution by passive diffusion for an estimated duration exceeding five years, remaining stable and active 21 . In vivo murine experiments showed eluted fulvestrant maintained preferential on target (e.g.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations